2010
DOI: 10.1074/jbc.m110.108514
|View full text |Cite
|
Sign up to set email alerts
|

Impaired de Novo Choline Synthesis Explains Why Phosphatidylethanolamine N-Methyltransferase-deficient Mice Are Protected from Diet-induced Obesity

Abstract: Phosphatidylcholine (PC) is synthesized from choline via the CDP-choline pathway. Liver cells can also synthesize PC via the sequential methylation of phosphatidylethanolamine, catalyzed by phosphatidylethanolamine N-methyltransferase (PEMT). The current study investigates whether or not hepatic PC biosynthesis is linked to diet-induced obesity. Pemt ؉/؉ mice fed a high fat diet for 10 weeks increased in body mass by 60% and displayed insulin resistance, whereas Pemt ؊/؊ mice did not.Compared with Pemt ؉/؉ mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
197
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(227 citation statements)
references
References 59 publications
(62 reference statements)
22
197
1
1
Order By: Relevance
“…Choline supplementation by others results in hepatic insulin resistance . Moreover, the impairment of de novo synthesis of choline via phosphatidylethanolamine N-methyltransferase, which catalyses the methylation of phosphatidylethanolamine in the liver, protects mice from diet-induced obesity (Jacobs et al 2010). However, in contradiction to the results of these studies, it has recently been reported that choline can promote liver health by maintaining cholesterol homoeostasis (Al Rajabi et al 2014).…”
Section: Sphingolipids and Phospho1contrasting
confidence: 42%
“…Choline supplementation by others results in hepatic insulin resistance . Moreover, the impairment of de novo synthesis of choline via phosphatidylethanolamine N-methyltransferase, which catalyses the methylation of phosphatidylethanolamine in the liver, protects mice from diet-induced obesity (Jacobs et al 2010). However, in contradiction to the results of these studies, it has recently been reported that choline can promote liver health by maintaining cholesterol homoeostasis (Al Rajabi et al 2014).…”
Section: Sphingolipids and Phospho1contrasting
confidence: 42%
“…The PEMT pathway is responsible for ;30% of hepatic PC synthesis; the remaining 70% is generated via the cytidine diphosphate-choline pathway (10). Unexpectedly, we reported that mice lacking PEMT are protected against high-fat diet (HFD)-induced obesity and IR (7). This protection was completely blunted when the diet was supplemented with choline, leading to the conclusion that PEMT provides an endogenous source of choline that supports normal weight gain (7).…”
mentioning
confidence: 71%
“…Therefore, abnormal lipid and glucose metabolism associated with IR and type 2 diabetes may be related to abnormalities in mitochondria. Hepatic phosphatidylcholine (PC) synthesis also has a role in the development of IR (7). PC is synthesized via the cytidine diphosphate-choline pathway (8).…”
mentioning
confidence: 99%
“…In the rat [24], hamster [25], dog [19] and monkey [26], choline deficiency results in liver dysfunction owing to accumulation of TG [27][28][29][30] and DAGs [31] within the hepatocyte. In rats, fatty liver begins within hours to days after initiation of a choline-deficient diet [32]. Also, fatty liver induced by a high fat diet in rats could be reversed by daily administration of choline for only 12 days [33].…”
Section: Animal Studiesmentioning
confidence: 94%